Health‐related quality of life in patients treated for nonfunctioning pituitary adenomas during the years 2000–2010. (7th December 2015) - Karppinen, Atte; Ritvonen, Elina; Roine, Risto; Sintonen, Harri; Vehkavaara, Satu; Kivipelto, Leena; Grossman, Ashley B.; Niemelä, Mika; Schalin‐Jäntti, Camilla
Summary: Objective: The published data on health‐related quality of life (HRQoL) after treatment of nonfunctioning pituitary adenomas (NFPAs) are conflicting. We evaluated HRQoL in a recent series of patients who had surgery for an NFPA. Design: Cross‐sectional study including a large control population. Patients and Measurements: A HRQoL questionnaire (15D) was sent to all patients ( n  = 161) having undergone transsphenoidal surgery for NFPA in the years 2000–2010 at the Helsinki University Hospital. The 15D score and dimension scores of the study population ( n  = 137) were compared with those of a large ( n  = 4967) gender‐ and age‐standardized control population. Possible independent predictors of HRQoL in the patients were estimated with multivariate regression analysis. Results: Postoperatively, 57% of the patients had normal visual function. After a mean follow‐up of 7·4 ± 3·2 years (mean ± SD), 62% suffered from hypopituitarism. Overall, HRQoL was near‐normal in patients compared to controls (15D scores 0·885 ± 0·114 vs 0·903 ± 0·093, respectively, P  = 0·07). On single dimensions, patients had impaired vision and sexual activity (both P  <   0·0005), more depression and distress (both P  <   0·005) and less discomfort and symptoms ( P  <   0·05). Age, body mass index, diabetes, depression and reoperation were independent predictors of impaired HRQoL (all P  <   0·05). Thyroxine substitution was associated with impaired and hydrocortisone and testosterone substitution (males only) with better HRQoL (all P  <   0·05). Conclusions: This recent series of NFPA patients demonstrates that overall HRQoL is near‐normal after medium term follow‐up; the most impaired dimensions were in vision and sexual activity. Comorbidities are strong predictors of impaired HRQoL.